Metered dose inhalers versus nebulizers for aerosol bronchodilator delivery for adult patients receiving mechanical ventilation in critical care units - Holland, Agi (Cochrane Database Syst Rev, 2013)
BACKGROUND: Nebulizers and metered dose inhalers (MDI) have both been adapted for delivering aerosol bronchodilation to mechanically ventilated patients, but there is incomplete knowledge as to the most effective method of delivery. OBJECTIVES: To compare the effectiveness of nebulizers and MDIs for bronchodilator delivery in invasively ventilated, critically ill adults. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2012, Issue 5); Ovid MEDLINE (1950 to Week 19 2012); Ovid EMBASE (1980 to Week 19 2012); CINAHL via EBSCOhost (1982 to Week 19 2012) and reference lists of articles. We searched conference proceedings and reference lists of articles. We also contacted manufacturers and researchers in this field. There were no constraints based on language or publication status. SELECTION CRITERIA: Randomized controlled trials (RCTs), including randomized cross‐over trials where the order of the intervention was randomized, comparing the nebulizer and MDI for aerosol bronchodilation in mechanically ventilated adult patients in critical care units. DATA COLLECTION AND ANALYSIS: Two authors independently assessed trial quality and extracted data. We contacted study authors for additional information where required. We collected information about adverse effects from the trials. MAIN RESULTS: This review included three trials, two addressing the primary outcome measure of a reduction of airway resistance (measured as a reduction in interrupter and additional airway resistance) with a total of 28 patients (n =10, n =18) and two addressing adverse changes to haemodynamic observations with a total of 36 patients (n =18, n =18). Limitations in data availability and reporting in the included trials precluded meta‐analysis and therefore the present review consisted of a descriptive analysis. Risk of bias in the included trials was judged as low or of unknown risk across the majority of items in the 'Risk of bias' tool. Cautious interpretation of the included study results suggests that nebulizers could be a more effective method of bronchodilator administration than MDI in terms of a change in resistance. No apparent changes to haemodynamic observations (measured as an increase in heart rate) were associated with either mode of delivery. Due to missing data issues, meta analyses were not possible. Additionally, small sample sizes and variability between the studies with regards to patient diagnoses, bronchodilator agent and administration technique mean that it would be speculative to infer definitive recommendations based on these results at this time. This is insufficient evidence to determine which is the most effective delivery system between nebuliser and MDI for aerosol bronchodilation in adult patients receiving mechanical ventilation. AUTHORS' CONCLUSIONS: Existing randomized controlled trials, including randomized cross‐over trials where the order of the intervention was randomized, comparing nebulizer and MDI for aerosol bronchodilation in mechanically ventilated adult patients do not provide sufficient evidence to support either delivery method at this time.